Cultural evolution of football tactics: strategic social learning in managers' choice of formation. (21st May 2020) - Mesoudi, Alex
Abstract: Abstract: In order to adaptively solve complex problems or make difficult decisions, people must strategically combine personal information acquired directly from experience (individual learning) and social information acquired from others (social learning). The game of football (soccer) provides extensive real world data with which to quantify this strategic information use. I analyse a 5-year dataset of all games ( n = 9127, 2012–2017) in five top European leagues to quantify the extent to which a manager's initial formation is guided by their personal past use or success with that formation, or other managers' use or success with that formation. I focus on the 4231 formation, the dominant formation during this period. As predicted, a manager's choice of whether to use 4231 is influenced by both their recent use of 4231 (personal information) and the use of 4231 in the entire population of managers in that division (social information). Against expectations, managers relied more on personal than social information, although this estimate was highly variable across managers and divisions. Finally, there did not appear to be an adaptive tradeoff between social and personal information use, with the relative reliance on each failing to predict managerial success.